POLA KONSUMSI PADA IBU HAMIL KEK DI WILAYAH KERJA PUSKESMAS TALAGA JAYA KABUPATEN GORONTALO - Ani Retni; Asni Ayuba; Yulianti Yunus (Universitas Muhammadiyah Gorontalo, 2020)
This research was conducted at Telaga Jaya community health centre work are, Gorontalo regency. The objective was to determine Consumption Patterns in Pregnant Women with Chronic energy deficiency. This research used qualitative with descriptive design. The result showed Consumption Patterns is the cause of chronic energy deficiency of the women. With the type of food that is often consumed is still less diverse and less energetic. The diet is still not good, most of the participants still rarely consume snacks and have the frequency and portion of one-sided tablespoons of food, also often consume tea every day which can reduce the absorption of red blood cells against iron which will be at risk of anemia. Fruits and vegetables are still lack with the reason that dislike and saving on buying food. The husband is also involved in his wife's pregnancy with her husband's low income causing a lack of purchasing nutritious food.